Pharmacoeconomic evaluation of the effectiveness of therapy for metastatic colorectal cancer - Yu. Yu. Petukhova; E. V. Eliseeva; M. V. Volkov; O. N. Li; A. G. Petukhova (Фармакоэкономика)
Objective: to perform a pharmacoeconomic evaluation of the effectiveness of therapies for metastatic colorectal cancer (mCRC) based on real practical data on medical help for patients with this disease.Material and methods. The authors performed a comparative cost-effectiveness analysis and the calculation of resource consumption in the application of several options of chemotherapy for mCRC: FOLFOX, FOLFIRI, and FOLFOXIRI; targeted therapy: FOLFOX + bevacizumab, FOLFOX + panitumumab, FOLFIRI + cetuximab, FOLFIRI + aflibercept, regorafenib monotherapy.Results. The cost-effectiveness parameter, calculated as a ratio of the cost of therapy to the median survival without progression, for chemotherapeutic schemes varied from 108 to 167 thousand rubles and for the targeted therapy schemes – from 223 to 930 thousand rubles. The calculation of resource consumption showed that in the case of a limited budget, 100% of patients can be treated by FOLFOX scheme, or 26% of patients by FOLFOX + panitumumab, or 47% of patients by FOLFOX + bevacizumab; and 100% of patients by FOLFIRI scheme or 11.5% of patients by FOLFIRI + cetuximab (aflibercept). Besides, it was established that in the case of a similar budget, 100% of patients with mCRC can be treated by chemotherapy schemes or a limited number of patients with regorafenib.Conclusion. The cost of targeted therapy significantly exceeds the cost of chemotherapeutic schemes. Still, considering the gross domestic product per capita in the Russian Federation, they can be an economically feasible investment and the optimum option of therapy